1977
DOI: 10.1111/j.1476-5381.1977.tb09735.x
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of Ion Transport and the Action of Ouabain in Heart Muscle

Abstract: I The influence of ouabain (0.4 jM) on contractile force and cellular Na and K concentrations was investigated in isolated left atria of the guinea-pig at rest and at different beat frequencies. Simultaneously the binding of ouabain to the tissue was determined. 2 Strict dependence of rates of onset of positive iontropic action and of binding of ouabain on beat frequency are limited to conditions where no alterations of cellular Na and K concentrations occur. A correlation was observed between sodium flux per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Cellular content of Na and K In separate experiments rat ventricular strips were prepared as described in the preceding paragraph and then exposed to ouabain for 30 min. Thereafter the strips were removed and processed as described previously (Bentfeld et al, 1977). Tissue electrolyte content was determined by means of atomic absorption spectroscopy using calibration curves for Na and K, which were established in each experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular content of Na and K In separate experiments rat ventricular strips were prepared as described in the preceding paragraph and then exposed to ouabain for 30 min. Thereafter the strips were removed and processed as described previously (Bentfeld et al, 1977). Tissue electrolyte content was determined by means of atomic absorption spectroscopy using calibration curves for Na and K, which were established in each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Effect ofouabain on the cellularK-and Na-content Ouabain intoxication in guinea-pig hearts has been shown to be parallelled by deterioration of the cellular electrolyte homeostasis (Bentfeld et al, 1977;Busse et al, 1979).…”
Section: Effect Ofouabain On Theforce Ofcontractionmentioning
confidence: 99%
“…Consequently, ouabain binding to intact cells (at low subtherapeutic concentrations, e.g. 10-8moll-1) is enhanced by raising intracellular [Na'] (Bentfeld et al, 1977;Temma & Akera, 1982;Kennedy et al, 1983). Alternatively, a compound reducing the 'Na-load' of the cell would be expected to reduce ouabain binding to intact cells.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation ofsarcolemmal membranes Sarcolemmal membranes were isolated from guinea-pig ventricles according to the method of Bers et al (1986 Bentfeld et al (1977).…”
Section: Methodsmentioning
confidence: 99%
“…However, measurement of intracellular sodium concentration ([Na]i), both chemically (Tuttle, Witt & Farah, 1961;Bentfeld, Lullmann, Peters & Proppe, 1977;GhyselBurton & Godfraind, 1979) or with sodium-sensitive microelectrodes (Ellis, 1977;Deitmer & Ellis, 1978) has shown that low steroid concentrations, while increasing contractile force, do not increase [Na], and may even decrease it. This does not refute the possibility that (as first suggested by Akera, Bennett, Olgaard & Brody, 1976) highly localized or transient increases in [Nal], that cannot be detected at present, do occur, but raises a reasonable doubt as to whether inhibition of the sodium pump is a prerequisite for the positive inotropic action of steroids (see also Okita, 1977).…”
Section: Introductionmentioning
confidence: 99%